2000
DOI: 10.1098/rspb.2000.1121
|View full text |Cite
|
Sign up to set email alerts
|

Depressed pollination in habitat fragments causes low fruit set

Abstract: In central New South Wales, Australia, £owers of Acacia brachybotrya and Eremophila glabra plants growing in linear vegetation remnants received less pollen than conspeci¢cs in nearby reserves. Pollen supplementation increased fruit production by both species, indicating pollen limitation of fruit set. Together these observations explain why fruit production by these species was depressed in linear-strip populations relative to nearby reserves. This study con¢rms that habitat fragmentation can lead to decline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
156
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(171 citation statements)
references
References 20 publications
11
156
1
3
Order By: Relevance
“…Lower fruit and seed set in plants of small habitat fragments have been observed for many species of tropical and temperate vegetation (e.g., Jennersten, 1988;Jennersten, & Nilsson, 1993;Aizen, & Feinsinger, 1994a;Byers, 1995;Oostermeijer, Altenburg, & den Nijs, 1995;Ågren, 1996;Cunningham, 2000;Quesada et al, 2003). Other species either do not show any different response in reproductive output between fragmented and continuous forest or present even higher reproductive output in smaller fragments and open areas than in continuous forest (e.g., Costin, Morgan, & Young, 2001;Dick, 2001;Lopes, & Buzato, 2007;Dunley et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lower fruit and seed set in plants of small habitat fragments have been observed for many species of tropical and temperate vegetation (e.g., Jennersten, 1988;Jennersten, & Nilsson, 1993;Aizen, & Feinsinger, 1994a;Byers, 1995;Oostermeijer, Altenburg, & den Nijs, 1995;Ågren, 1996;Cunningham, 2000;Quesada et al, 2003). Other species either do not show any different response in reproductive output between fragmented and continuous forest or present even higher reproductive output in smaller fragments and open areas than in continuous forest (e.g., Costin, Morgan, & Young, 2001;Dick, 2001;Lopes, & Buzato, 2007;Dunley et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Abiotic changes caused by habitat fragmentation may also affect the predation rate on plant reproductive structures owing to changes in the local animal community (Cunningham, 2000). Seed predation is an important ecological interaction that may directly impact plant fertility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the effects of inbreeding, enhanced by fragmentation, are possible causes for the observed low reproductive vigor. Cunningham (2000), who studied plants of Acacia brachybotrya from fragments of vegetation in Australia, observed a lower number of pollen grains in the anthers of samples from the fragmented populations than those of samples from populations of large reserves. They also observed a decrease in fruitfulness of the populations in fragmented areas.…”
Section: Effect Of Forest Fragmentation On Microsporogenesis In E Unmentioning
confidence: 99%
“…It is also just as important for those working in conservation. Increasingly, fragmented habitats threaten the survival of many acacias, particularly in the Wheat Belt region of Western Australia (Cunningham 2000a(Cunningham , 2000b, and difficult decisions must be made about where limited resources for conservation and environment restoration should be invested. Population genetic methods provide the best available approach for assessing patterns of genetic diversity within species, and so provide a means to prioritise populations for protection (Crandall et al 2000).…”
mentioning
confidence: 99%